Overuse injuries in long distance running - a literature review on risk factors - Vijayan, G.; Murali Rajan, K. (Indian Journal of Applied Research, 2019)
INTRODUCTION: In the past three decades, the incidence of running-related overuse injuries has significantly increased because of the increasing number of recreational athletes and higher training intensity in competitive athletes. Long distance running has gained popularity in recent years, but between 19.4 and 79.3% of runners sustain a running related injury every year. Various risk factors contribute to the occurrence of this issue and shoe modifications are thought to be an efficient tool in managing running related over use injuries. The aim of this study was to collect and review information about the risks factors of overuse injuries long distance running. METHODOLOGY: A systematic search of the electronic database of PUBMED, Bireme and PEDro which were selected that addressed clinical trials, control cases, prospective and cross-sectional studies. RESULTS: The search yielded 246 references. A predefined inclusion criteria (case studies, clinical trials, prospective studies, cross sectional studies that addressed adult runners either amateur or professional) was used and 51 articles remained. 18 citations were excluded and 20 articles were after reading the abstract and full text. Therefore 13 studies that met the criteria for analysis were included. CONCLUSION: The overuse injuries are very much prevalent in long distance runners and the ethology is multifactorial. The distance, terrain, weekly sessions and history of previous injuries are the risk factors that in?uence the occurrence of these injuries.